Albergar o longínquo: uma proposta de transcrição para violão da Fuga BWV 995, de J. S. Bach, em diálogo com a tradutologia de Antoine Berman - Ricardo Marçal de Souza e Silva (2024)
The recent developments in the dialogue between theoretical research on musical transcription and tradutology have resorted to the thinking of the French philosopher Antoine Berman (1942-1991) to develop an ethical dimension in its propositions that reveals, manifests and embraces the foreignities of a given work. The present investigation, focusing on the Fugue BWV 995 by Johann Sebastian Bach (1685-1750), proposes the composer's suites attributed to the lute – BWV 823, 995, 996, 997 and 1006a – as a potentially fertile field for experimentation of such ideas: the realization of their organological indefiniteness keeps them suspended in a state of transitivity favorable to transcriptional experiments that not only employ the composer's language – the architectural organicity of its musical materials – but also make use of an essential principle underlying its creation: the inventio (“invention”).